Análise espacial dos acidentes de trânsito do município de Fortaleza - Queiroz, Marcelo Pereira (2003)
Traffic accident indexes have been used to characterize the traffic safety conditions in countries, states and cities, allowing comparisons among them and with international standard indexes. Besides, the indexes are used to evaluate the results of the treatment measures implemented in the street network by the traffic management department. With the integration of the Geographical Information Systems (GIS) to a group of more robust tools of spatial analysis, various indexes can be determined and analyzed ina more efficient way, taking into account the spatial attribute of the accidents phenomenon. The main objective of this work was to geographically analyze such a phenomenon, beginning with the implementation of a geocoded database of traffic accidents and, then, applying and demonstrating the potential of spatial analysis and statistical tools for the area of traffic safety. These tools were used to develop a systemic spatial characterization of the safety conditions over the street network, making it possible to identify critical spots and to provide more information to subsidize the decision making process at the traffic management department. As a sample application, this study considered the traffic accident data of Fortaleza’s Traffic Accident Information System (SIAT -FOR), geocoded using a routine developed in a GIS programming language. It is believed that the main contribution of this research was to bring a new critical thinking to the treatment of the quantitative geographical information within th e broader area of transportation engineering and, specifically, in dealing with traffic safety issues. This way of thinking comes from the recognition of the spatial nature of transport data and gets consolidated in the many possibilities of applying the spatial analysis and statistical tools that rise from the digital environment.